Manifestations of Jeremy Bentham’s legal utilitarianism: A critical study - Said Mina , Rawa Kakarash; Rsul Murad , Hemin; Mala Aziz , Sardar (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
Utilitarianism is a moral theorythat descends from the view that everything is subject to the motives of pleasure and pain. Jeremy Bentham developed this theory byputting human nature under the rule of pleasure and pain,whilecalling for happiness for the greatest number of people. The utility to Bentham is that property isan object which tends to produce benefit, advantage, good or happiness. Therefore, the law to Bentham is what comes only from the will of the authority, providedthat the authority does not make a mistake and is the only authority capable of recognizing and knowing what works are beneficial for individuals and what harms them. He may refuse religion, morality, or values to guide behaviour other than pleasure, which is the sole purpose of life and, together with the pain, determines what we do and what we ought to do. Accordingly, he did not give any value to duty. He also gave anumerical value to pleasure by identifying the factors that depend on it to calculate pleasure, which was not without criticism. In his philosophy, Benthamfailed in combining or bringing the private and public interests together.